Lymphocyte proliferation in mice congenitally deficient in T-cell receptor alpha beta + cells. - Viney, J L (1994)
In mice and humans, T cells are characterized on the basis of T-cell receptor (TcR) expression and divided into the major TcR alpha beta + and minor TcR gamma delta + populations. TcR alpha beta + cells are considered to be the primary regulators of the immune response, whereas the function of TcR gamma delta + cells is unclear. Mice congenitally deficient in TcR alpha beta-expressing cells provide an ideal model for analyzing the independent in vivo function of TcR gamma delta + cells in the absence of TcR alpha beta + cells. Here we report that lymphoid organs in TcR alpha mutant mice undergo substantial enlargement after being challenged by environmental antigens. This organ expansion can be attributed in part to increases in the relative proportions and absolute numbers of TcR gamma delta + cells, but an expansion of the recently described TcR beta + alpha - population also has a role. The expansion of the TcR gamma delta + population is polyclonal, as evidenced by the usage of multiple gamma and delta variable chain segments. Furthermore, a substantial proportion of the cells appears to be activated and these activated cells express surface activation markers. The results clearly demonstrate that TcR gamma delta + cells proliferate independently in response to a broad spectrum of challenges. Moreover, since the expansion of the lymphoid tissues and the TcR gamma delta + cell population is excessive relative to that seen in wild-type animals, one role of TcR alpha beta + cells is directly or indirectly to limit the responses of the other lymphoid components.